Analysis of the time‐domain model of the LLC series resonant converter with frequency and single phase shifted control - Tengfei Guo; Pengyu Jia; Xuan Zhang; Yajing Zhang; Xiaoyu Zhu (IET Power Electronics, 2024)
Abstract LLC series resonant converter (LLC‐SRC) has attracted much attention due to its simple circuit structure and easy realization of soft‐switching. To get a better efficiency, rectifier stage can be realized by the active switches instead of the diodes. Meanwhile, more control variables can be selected besides the switching frequency, such as single phase shifted (SPS) angle, dual phase shifted (DPS) angle, and extended phase shifted (EPS) angle. Considering the simplicity of the implementation of the control strategy, this paper focused on the converter model with frequency and SPS control. Different from the common modelling method with the Fundamental Harmonic Approximation (FHA), the precise time‐domain mathematic model is built. By a comparison between the two modelling results, it can be proved the FHA model may be failure in some operating condition while the proposed time‐domain model can still show a good accuracy. According to the proposed model, two simple fixed‐frequency SPS control strategies are proposed. The first one can realize infinite soft‐switching margin with no restrictions on the transformer magnetizing inductance. The second one can greatly improve the efficiency of the converter. All the theoretical results are verified by a 1‐kW experiment prototype.